Perkembangan E-Learning Di Indonesia - Bustani; Husnul Faizin; Muhammad (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2023)
This paper aims to describe the use of e-learning for teaching in Indonesia. The presence of E-Learning as one of the products of information technology is one of the solutions to the problems of education in Indonesia. Rapid technological developments in other parts of the world are also felt in Indonesia, although the use of e-learning for learning in Indonesia has not been a satisfactory result, but at least the future will continue to be efforts to maximize the potential of education.